Inosine Accelerates the Regeneration and Anticipates the Functional Recovery after Sciatic Nerve Crush Injury in Mice. (15th December 2019) - Soares dos Santos Cardoso, Fellipe; Cardoso, Ricardo; dos Santos Ramalho, Bruna; Bastos Taboada, Tiago; dos Santos Nogueira, Ana Carolina; Blanco Martinez, Ana Maria; Martins de Almeida, Fernanda
Highlights: Inosine was injected intraperitoneally after sciatic nerve injury. Inosine treatment was able to promote neuroprotection. Inosine accelerates the regeneration and reduced macrophage immunostaining. Inosine anticipates functional recovery. Abstract: Trauma to the peripheral nervous system (PNS) results in loss of motor and sensory functions. After an injury, a complex series of events begins, allowing axonal regeneration and target reinnervation. However, this regenerative potential is limited by several factors such as age, distance from the lesion site to the target and severity of lesion. Many studies look for ways to overcome these limitations. Inosine, a purine nucleoside derived from adenosine, emerges as a potential treatment, due to its capacity to regulate axonal growth, neuroprotection and immunomodulation, contributing to motor recovery. However, no studies demonstrated their effects on PNS. C57/Black6 mice were submitted to sciatic nerve crush and received intraperitoneal injections of saline or inosine (70 mg/kg), one hour after injury and daily for one week. To evaluate axonal regeneration and functional recovery, electroneuromyography, Sciatic Function Index (SFI), rotarod and pinprick tests were performed. Our results showed that the inosine group presented a higher number of myelinated fibers and a large amount of fibers within the ideal G-ratio. In addition, the results of electroneuromyography showed greater amplitude of the compound muscle action potentials in the first and second weeks, suggesting anticipation of regeneration in the inosine group. We also observed in the inosine group, motor and sensory neurons survival, reduction in the number of macrophages and myelin ovoids in the sciatic nerves, and an early recovery of motor and sensory functions. Thus, we conclude that the use of inosine accelerates axonal regeneration promoting an early recovery of motor and sensory functions.